Adopting price-level targeting under imperfect credibility in ToTEM - Gino Cateau; Oleksiy Kryvtsov; Malik Shukayev; Alexander Ueberfeldt (Bank of Canada, 2009)
Using the Bank of Canada's main projection and policy-analysis model, ToTEM, this paper measures the welfare gains of switching from inflation targeting to price-level targeting under imperfect credibility. Following the policy change, private agents assign a probability to the event that the policy-maker will revert to inflation-targeting next period. As this probability decreases and imperfect credibility abates, inflation expectations in the economy become consistent with price-level targeting. The paper finds a large welfare gain when imperfect credibility is short-lived. The gain becomes smaller with persisting imperfect credibility, turning to a loss if it lasts more than 13 years.
Keywords: E31; E52; 330; Monetary policy framework; Monetary policy implementation; Geldpolitik; Inflation Targeting; Preisniveaustabilität; Unvollkommene Information; Wohlfahrtseffekt; Kanada